Organization and multiple regulation of histidine utilization genes in Pseudomonas putida. - Hu, L (1988)
The arrangement of the histidine utilization (hut) genes in Pseudomonas putida was established by examining the structure of a DNA segment that had been cloned into Escherichia coli via a cosmid vector. Southern blot analysis revealed that the restriction patterns of the hut genes cloned into E. coli and present in the P. putida genome were identical, indicating that no detectable DNA rearrangement took place during the cloning. Expression of the hut genes from a series of overlapping clones indicated the gene order to be hutG-hutI-hutH-hutU-hutC-hutF. The transcription directions of the different hut genes were determined by cloning the genes under control of the lambda pL promoter. This showed that hutF, encoding formiminoglutamate hydrolase, was transcribed in a direction opposite to that of the other genes. Inactivation of the cloned hut genes by Tn1000 insertion revealed that the hut genes were divided into three major transcriptional units (hutF, hutC [the repressor gene], and hut UHIG), but hutG may also be independently transcribed. When cloned individually with hutC on the same vector, hutF and hutU (which encodes urocanase) expression was induced by urocanate, indicating that these two genes each possess an operator-promoter element. Tn1000 insertions (in the cloned genes) or Tn5 insertions (in the P. putida genome) affecting the hutI or hutH gene only partially eliminated hutG expression. Furthermore, hutG, which specifies N-formylglutamate amidohydrolase, was regulated by the hutC product when the two genes were cloned on the same vector and expressed in E. coli. Therefore, hutG can be expressed independently from its own promoter, in keeping with earlier observations that N-formylglutamate amidohydrolase synthesis is not coordinated with that of urocanase and histidase and can be induced by N-formylglutamate or urocanate.